Long term patient reported swallowing function following chemoradiotherapy for oropharyngeal carcinoma. Issue 3 (September 2018) - Dixon, Lynne; Ramasamy, Satiavani; Cardale, Kate; Dyker, Karen; Garcez, Kate; Lee, Lip Wai; McPartlin, Andrew; Murray, Patrick; Sen, Mehmet; Slevin, Nick; Sykes, Andrew; Prestwich, Robin; et al.
Abstract: Background and purpose: Limited data are available to inform on long term swallowing outcomes following concurrent chemoradiotherapy for oropharyngeal carcinoma. The aims of this study are to determine long term patient-reported swallowing outcomes across two large UK centres in routine clinical practice and identify associated factors. Material and methods: All patients treated for oropharyngeal squamous cell carcinoma with concurrent chemoradiotherapy, and irradiation of the bilateral neck, between 2011 and 2013 were identified. Those requiring therapeutic enteral feeding prior to treatment, or having subsequent disease relapse, were excluded from the study. Patients were sent postal invitations to complete the MD Anderson Dysphagia Inventory (MDADI), at least two years following completion of treatment. Results: Completed MDADI were received from 201/242 eligible patients (83%) at a median of 3.4 years (range 2–5) post treatment. Median composite MDADI score was 68.4. 64 (32%) had composite MDADI <60 classed as 'poor' function, 76 (38%) scores ≥60–<80 classed as adequate function, and 61 (31%) had scores ≥80 classed as optimal function. Patients with normal and abnormal pre-treatment diet had median composite MDADI scores of 70.5 versus 47.4 respectively. Patients who did not require enteral feeding during treatment and those who did had median composite MDADI scores of 76.3 versus 65.3 respectively. On multivariate analysis poorer performance status, abnormal pre-treatment diet, and use of enteral feeding during radiotherapy were all significantly associated with lower composite, global and subscale MDADI scores. Conclusions: Patient reported swallowing dysfunction remains common in the long term post-chemoradiotherapy. Impaired pre-treatment diet and use of enteral feeding during treatment are key factors associated with poorer swallowing outcomes.